Penguatan Kepemimpinan Kelembagaan Pembentukan Kelompok Tani Kapulaga ”Sedulur Laga” di Desa Kandangan Kecamatan Senduro Kabupaten Lumajang - Ivana Septia Maharani; Asmuni Asmuni; Ahmad Ihsa Restu Alifin (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2026)
This community service program aims to strengthen institutional leadership through the establishment of the